Ferroelectric α-In2Se3 Wrapped-Gate β-Ga2O3 Field-Effect Transistors for Dynamic Threshold Voltage Control - Yang, Jeong Yong; Yeom, Min Jae; Park, Youngseo; Heo, Junseok; Yoo, Geonwook (Advanced Electronic Materials, 2021)
Indium selenide (α-In2Se3), which is a recently emerging ferroelectric semiconductor, can solve a major hindrance to applications of an ultra-wide bandgap beta-gallium oxide (β-Ga2O3) semiconductor. Here, ferroelectric α-In2Se3 wrapped-gate β-Ga2O3 field-effect transistors (FETs) for dynamic threshold voltage (VTH) control is demonstrated. The dry-transferred α-In2Se3 layer is wrapped around β-Ga2O3 channel, which allows efficient electrostatic gate modulation. Thus, the ferroelectricity of α-In2Se3 and a thin native oxide interlayer formed at the interface between β-Ga2O3 and α-In2Se3 can provide effective VTH control. Applying a positive voltage pulse to the gate electrode induces positive VTH shift; hence, the device can be even changed from depletion to enhancement (E-) mode. The E-mode β-Ga2O3 FET exhibits steep-subthreshold slope with a negligible hysteresis. The VTH of E-mode can be further modulated by applying back-gate bias, and electrical performance can be enhanced via dual-gate operation. The approach demonstrates an energy efficient β-Ga2O3-based switching device architecture integrated with ferroelectric van der Waals 2D materials.
Keywords: Dynamic threshold; Electrical performance; Electrostatic gates; Ferroelectric semiconductors; Field effect transistor (FETs); Positive voltage; Subthreshold slope; Switching devices; beta-gallium oxide; ferroelectric; indium selenide; threshold voltage control; wrapped-gate structure